Strengthening community empowerment for elderly health service in new normal by Pol-Sadar (Integrated Health Service Post for Elderly) - Umi Hani; Fery Agusman Motuho Mendrofa (Journal of Community Empowerment for Health, 2023)
Introduction: Before the pandemic, older people actively participated in an integrated health service post named POSYANDU. This high participation is due to community health workers who understand their role in realizing basic health services. During the pandemic, POSYANDU must be held with attention to developments in the COVID-19 case. Methods: We implemented the online-based service of integrated health posts to provide online health services for older people. This paper explains the participation of elders, family, and community health workers in the revitalization strategies of integrated health service activities for older people during the pandemic. The activities included health assessments via telemedicine (video call), drive-thru services for vital signs assessment and simple lab checks, home visits, and education via WhatsApp as needed. The implementation began in June 2020 and in May 2021 with 184 older people in some places in Central Java, including Semarang City, District of Semarang, and District of Batang. We also worked with teaching volunteers consisting of five community health workers and 19 nursing students in the community. Results: The results of these activities were the findings of health problems experienced by the elderly during the pandemic (depression, hypertension, and joint stiffness), increased knowledge, and physical activity of the elderly group. The 100 older people participated in online exercise activities accompanied by their families. They felt a decrease in complaints of joint stiffness, and 84 older adults participated in health education and exercise activities in open areas by implementing strict health protocols. Most participants said they were satisfied with Pol-Sadar activities as a health service strategy for older people during the pandemic. Conclusion: In conclusion, the online program was effective as a strategy of health services for the elderly, especially during the new normal era, and increased the participation of family and community health workers, but it needs adequate devices to participate.